Pelaksanaan Restorative Justice di Tinjau dari Hukum Pidana yang Berlaku di Indonesia - Pieter Leonardo; Hery Firmansyah (Syntax Literate, 2023)
Restorative justice is basically a concept to restore the impact of a crime. This concept emerged due to the inability of the previous concept to accommodate the interests of the victim. One application of restorative justice that has recently occurred is the case of the police attack carried out by a female student with the initials HFR. The formulation of the problem raised is how to implement restorative justice according to criminal law in Indonesia and whether it is appropriate to apply restorative justice in the case of: assault by an officer while on duty. This research uses normative research with the nature of descriptive analytical research using secondary data collected by the technique of literature study and analyzed by deductive logic. The results of the research show that the concept of restorative justice in Indonesia has been applied in all lines of law enforcement, starting from the juvenile justice system, the scope of general justice, the prosecutor's office, the police, regional regulations to the penitentiary. Even though the provisions stipulated by each institution are still not in accordance with the standards. In addition, the application of restorative justice in this assault case actually fulfills the requirements and eligibility to carry out restorative justice, but on the other hand, restorative justice is carried out only as a "peaceful" effort without any real form of accountability from the perpetrator to restore the loss and damage suffered by the victim.